Four-wave mixing cascades seeded by a multiwavelength Brillouin–erbium fiber laser - Ahmad, Nurul 'Atiqah; Dahlan, Samsul Haimi; Cholan, Noran Azizan (IOP Publishing, 2018)
Four-wave mixing (FWM) cascades which are seeded by a multiwavelength Brillouin–erbium fiber laser (MBEFL) are experimentally demonstrated in this work. The MBEFL, which is based on virtual mirror feedback, is successful in providing the seed for the FWM cascades. The stimulated Brillouin scattering and parametric gain for the development of the MBEFL and FWM cascades, respectively, are provided by a 12 km dispersion-shifted fiber (DSF). By launching the MBEFL into the DSF, as many as 80 comb lines can be generated when the Brillouin pump (BP) wavelength is tuned at 1560 nm. Analysis of FWM cascades as a function of BP wavelength shows that the number of comb lines is greater at the anomalous-dispersion region of the DSF, suggesting that the phase mismatch is minimized in that regime.